Vincristine-associated Neuropathy With Antifungal Usage: A Kaiser Northern California Experience. Issue 5 (July 2018) - Nikanjam, Mina; Sun, Aida; Albers, Mark; Mangalindin, Kristine; Song, Eyun; Vempaty, Hyma; Sam, Danny; Capparelli, Edmund V.
Abstract : The dose-limiting toxicity for vincristine is peripheral neuropathy which can be potentiated with concurrent usage of azole antifungals. The current retrospective study assessed the incidence of concurrent vincristine and azole antifungal usage to determine if it led to increased neurotoxicity for the Kaiser Northern California pediatric acute lymphoblastic leukemia (ALL) and Hodgkin lymphoma patient population. Data were obtained from the electronic medical record (2007 to 2014). In total, 130 subjects received at least one dose of vincristine for ALL or Hodgkin lymphoma (median age 9, 88% ALL, 58% male, 47% Caucasian). Thirty one percent of patients received concurrent antifungal usage (fluconazole, 78%; voriconazole, 10%; fluconazole/voriconazole, 12%); however, concurrent antifungal usage accounted for <15% of vincristine doses. Grade 2 or greater neuropathy occurred in 51% of patients; grade 3 neuropathy was present in 8% of patients. No difference in the incidence of grade 2 or greater neuropathy was observed with the concurrent use of antifungal therapy ( P =0.35), sex ( P =0.59), type of cancer ( P =0.41), ethnicity ( P =0.29), or age ( P =0.39), but was higher with increasing amount of vincristine doses ( P =0.004). These results suggest that concurrent azole antifungal usage with vincristine for patients with ALL and Hodgkin lymphoma was low in the Kaiser Northern California population and limited usage as needed may be reasonable and safe.